Trends in Indications and Techniques of Corneal Transplantation from 1999 through 2015 at a Tertiary Referral Center in Athens, Greece - Konstantinos Droutsas; Georgios Bagikos; Dimitrios Miltsakakis; Ilias Georgalas; Apostolos Lazaridis; Klio Chatzistefanou; Marilita M. Moschos; Chryssanthi Koutsandrea; Georgios Kymionis (Journal of Ophthalmology)
Introduction. During the past decade, novel techniques of corneal transplantation allowing faster and better restoration of vision have emerged. The present cohort study describes a shift of indications and techniques that has occurred in the field of corneal transplantation over a 17-year period in Greece. Methods. All patients undergoing keratoplasty between January 1999 and December 2015 at an academic tertiary referral center in Athens, Greece, were retrospectively reviewed. The annual incidence of keratoplasty indications and techniques was recorded and analyzed. Results. A total of 1382 keratoplasty procedures were included. Leading indications were bullous keratopathy (BK) (37.5%), followed by allograft rejection (17.7%), corneal scar (12%), keratoconus (KC) (10.3%), and Fuchs endothelial dystrophy (FED) (8.8%). A decreasing trend was observed for KC (P=0.009) and an increasing trend for BK (P=0.003) and FED (P=0.001). In 2015, the incidence of penetrating keratoplasty (PK) had decreased from 100% (1999 to 2009) to 21.4%; for cases with isolated pathology of the corneal endothelium, DSAEK was the preferred technique (59.8%), while the respective rate of DMEK was 18.8%. Conclusion. Herein, we observed an increasing trend of endothelial pathology among keratoplasty indications as well as a major shift in preferred techniques due to a wide adoption of the new EK procedures.